Transcriptional and metabolic remodeling in clear cell renal cell carcinoma caused by ATF4 activation and the integrated stress response (ISR). Issue 9 (21st June 2022) - van der Mijn, Johannes C.; Chen, Qiuying; Laursen, Kristian B.; Khani, Francesca; Wang, Xiaofei; Dorsaint, Princesca; Sboner, Andrea; Gross, Steven S.; Nanus, David M.; Gudas, Lorraine J.
Abstract: Research has shown extensive metabolic remodeling in clear cell renal cell carcinoma (ccRCC), with increased glutathione (GSH) levels. We hypothesized that activating transcription factor‐4 (ATF4) and the integrated stress response (ISR) induce a metabolic shift, including increased GSH accumulation, and that Vitamin A deficiency (VAD), found in ccRCCs, can also activate ATF4 signaling in the kidney. To determine the role of ATF4, we used publicly available RNA sequencing (RNA‐seq) data sets from The Cancer Genomics Atlas. Subsequently, we performed RNA‐seq and liquid chromatography–mass spectrometry‐based metabolomics analysis of the murine TRAnsgenic Cancer of the Kidney (TRACK) model for early‐stage ccRCC. To validate our findings, we generated RCC4 cell lines with ATF4 gene edits (ATF4‐knockout [KO]) and subjected these cells to metabolic isotope tracing. Analysis of variance, the two‐sided Student's t test, and gene set enrichment analysis were used ( p < 0.05) to determine statistical significance. Here we show that most human ccRCC tumors exhibit activation of the transcription factor ATF4. Activation of ATF4 is concomitant with enrichment of the ATF4 gene set and elevated expression of ATF4 target genes ASNS, ALDH1L2, MTHFD2, DDIT3 ( CHOP ), DDIT4, TRIB3, EIF4EBP1, SLC7A11, and PPP1R15A ( GADD34 ). Transcript profiling and metabolomics analyses show that activated hypoxia‐inducible factor‐1α (HIF1α) signaling in our TRACK ccRCC murine model also induces an ATF4‐mediated ISR. Notably, both normoxic HIF1α signaling in TRACK kidneys and VAD in wild‐type kidneys diminish amino acid levels, increase ASNS, TRIB3, and MTHFD2 messenger RNA levels, and increase levels of lipids and GSH. By metabolic isotope tracing in human RCC4 kidney cancer parental and ATF4 gene‐edited (ATF4‐KO) cell lines, we show that ATF4 increases GSH accumulation in part via activation of the mitochondrial one‐carbon metabolism pathway. Our results demonstrate for the first time that activation of ATF4 enhances GSH accumulation, increases purine and pyrimidine biosynthesis, and contributes to transcriptional and metabolic remodeling in ccRCC. Moreover, constitutive HIF1α expressed only in murine kidney proximal tubules activates ATF4, leading to the metabolic changes associated with the ISR. Our data indicate that HIF1α can promote ccRCC via ATF4 activation. Moreover, lack of Vitamin A in the kidney recapitulates aspects of the ISR.